Conformidade entre ideia e objeto : reflexão sobre a verdade na I apologia de Justino Mártir - Wingert, Diego dos Santos (2019)
This dissertation presents a bibliographical research directed to establish the moral and dogmatic identification of the term Truth, exposed in a predicative way in the work entitled I Apology of Justin Martyr. It is believed that in the formation and historical constitution of Christianity some authors like Justin of Rome helped to create and foster the parameters necessary to establish a "Christian identity" during the first two centuries of the present era. From new values and precepts, an attempt to recognize and distinguish the fact of being Christian amidst the socioreligious context of the Greco-Roman "world" was pragmatically ordered. Explicitly and implicitly - and sometimes in a paradoxical way - Justin categorically identifies what it was like to be a follower of Christ in his Apology, in addition to presenting what could be categorically and even tangibly Truth in that process. From this idea of faith, the dissertation discusses pertinent questions about the author, the base work and other characteristics of its historical context. The relations between the Hellenic culture and the new modus vivendi in that environment were investigated, and in it the philosophical identity of Justin. Finally, a clarifying picture was presented on the elements that are considered unquestionable evidences for Justino of what is the Truth revealed among men. In this way, a probable definition of the Truth according to the conception of Justin Martyr from his I Apologia was developed.